Beyond the preschool gate: teacher pedagogy in the Australian 'bush kinder'. Issue 1 (2nd January 2023) - Speldewinde, Christopher; Kilderry, Anna; Campbell, Coral
ABSTRACT: Research into pedagogical approaches used in early years' nature education, more specifically European and UK forest schools, remains according to Leather, 'undertheorised.' In a similar situation in Australia, the bush kindergarten programmes (referred to as 'bush kinders'), have had limited research attention. Influenced by European and UK forest school approaches, bush kinders are a recent development in Australian early years nature education. We discuss an ethnographic study where teaching and learning in three bush kinder settings was observed, each with different pedagogical approaches. The paper reports one main finding, where a wide range of pedagogical approaches were observed across the different bush kinder sites. To theoretically frame these pedagogical approaches, our analysis builds on Edwards' notion of play-based learning, along with a model of inquiry-based teaching proposed by Furtak et al. Using ethnographic methods we draw on fieldwork data and research literature to analyse bush kinder pedagogies. The paper contributes to the conceptualisation of pedagogy in early childhood nature and bush kinder programmes.